PENGABAIAN HAK REPRODUKSI PEREMPUAN SEBAGAI PEMICU PERCERAIAN - Nuryasni Yazid (Institut Agama Islam Negeri Batusangkar, 2022)
This paper aims to prove that neglect of women's reproductive rights is a trigger for divorce. The method used in this paper is descriptive analytic by describing what data is obtained from the literature related to this study, which is then analyzed until it is found that there are four reproductive rights of women; First, the right to choose a partner. second, the right to enjoy sexual relations. third, the right to determine pregnancy. fourth, the right to nurture and care for children. These four rights must be owned proportionally by women as bearers of the reproductive mandate so that the household runs in harmony and balance.